A Stylistic Study on the Syntactic Level of Arundhati Roy’s The God of Small Things and Translation Strategies in the Thai Translated Version - Tultrairatana, Sasipa (Language and Linguistics, 2023)
Style is one of the most important literary elements in literature. It reflects the author’s identity and unique way of writing. Therefore, a stylistic study is an interesting and important topic for linguistic analysis. The objectives of this research are to identify and analyze: 1) the writing styles at the syntactic level that are related to the post-colonial concept in Arundhati Roy's The God of Small Things, and 2) the translation strategies used by the Thai translator, Sodsai, including analyzing which strategies help to maintain the meaning and the author’s unique writing styles at the syntactic level. The results reveal that the samples of the writing style at the syntactic level related to the post-colonial concepts can be divided into seven categories: passive voice sentences, active voice sentences, English-Malayalam code-switching, using the tag “isn't it” in every context, negative sentences, sentences with similes and metaphors, and topicalization. The translator applied various translation strategies including literal translation, adaptation, unit shift, loan translation, colloquialization, neutralization, level shift, addition, omission, pronominalization, and nonpronominalization to convey the meaning and maintain the specific style.